PENGARUH CITRA MEREK, KUALITAS DAN PROMOSI TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA PT NIPPON PAINT DEPOT YOGYAKARTA (Jurnal Riset Manajemen Akuntansi Indonesia, 2026)
This study aims to analyze the influence of brand image, quality, and promotion on consumer loyalty, both directly and indirectly through consumer satisfaction as an intervening variable at PT Nippon Paint Depot Yogyakarta. The background of this study is based on the importance of consumer loyalty in maintaining business sustainability, as well as the role of marketing strategy in shaping consumer satisfaction and loyalty. This study uses a quantitative approach with a survey method. The sample used was 105 respondents who were consumers of PT Nippon Paint Depot Yogyakarta, with a sampling technique using purposive sampling. Data collection was carried out by distributing questionnaires. The data analysis method used was Structural Equation Modeling (SEM) Partial Least Square (PLS). The results showed that brand image does not have a positive effect on customer loyalty. Quality does not have a positive effect on loyalty. Promotion does not have a positive effect on loyalty. Consumer satisfaction does not act as a mediating variable on the influence of brand image on loyalty. Consumer satisfaction does not act as a mediating variable on the influence of quality on loyalty. Consumer satisfaction acts as a mediating variable in the influence of brand image on loyalty. Based on these findings, companies are advised to continue to strengthen brand image and maintain product quality in order to increase consumer satisfaction and loyalty. Promotion strategies also need to be evaluated and adjusted to be more effective in building long-term relationships with consumers.
Keywords: Brand Image; Quality; Promotion; Consumer Satisfaction; Consumer Loyalty